HUBUNGAN LINGKUNGAN PEMBELAJARAN PADA SISTEM PEMBELAJARAN KURIKULUM BERBASIS KOMPETENSI DENGAN TINGKAT GEJALA DEPRESI DAN TINGKAT GEJALA CEMAS PADA MAHASISWA ANGKATAN 2017-2020 FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA AMBON - Jeremy Mairuhu; Sherly Yakobus; Laura B S Huwae (PAMERI, 2022)
The learning environment is a manifestation of a curriculum, so that the ward assessment in a medical institution is part of the implementation of the curriculum evaluation. Today medical faculty uses the new curriculum, a competency-based or KBK curriculum system that was released in 2005. There is a report on the prevalence of depression and anxiety disorder was achieved in medical students first and last year. The aim of researchers is to know about the competency-based curriculum learning system with the level of depression and anxiety for 2017-2020 students of Pattimura University specially Faculty of Medicine. The results of the analysis in this study indicate that there is no relationship between the learning environment in the competency-based curriculum learning system with levels of depression symptoms (p=0,090) and levels of anxiety symptoms (p=0,076) in students of class 2017-2020, Faculty of Medicine, University of Pattimura, Ambon. This study has limitations, namely researchers cannot reach respondents directly because during the covid-19 pandemic, and lecture activities are not carried out face-to-face, so respondents may fill out questionnaires carelessly and are not honest in filling out the questionnaires provided.